(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article reveals the origin of folk pedagogy, its content, as well as the issues of taking into account the experience of folk pedagogy in the formation of individual personality characteristics of students and their effective use in the development and implementation of modern pedagogical principles and theories.